Serum alkaline phosphatase predicts survival outcomes in patients with skeletal metastatic nasopharyngeal carcinoma - Ying Jin (Clinics, 2015)
OBJECTIVE: Bone metastasis is frequently associated with nasopharyngeal carcinoma. The diagnosis and follow-up of bone metastatic patients usually relies on skeletal X-ray and bone scintigraphy, which are time-consuming and costly. This study aimed to evaluate whether serum alkaline phosphatase offers clinical value in predicting the clinical response and survival outcome for skeletal metastatic nasopharyngeal carcinoma. METHODS: Serum alkaline phosphatase was measured at baseline and then before each cycle of treatment in 416 nasopharyngeal carcinoma patients with bone metastasis. The correlations between the pre-treatment and post-treatment alkaline phosphatase levels and the treatment efficacy were analyzed using the chi-square test. Survival was analyzed using the Kaplan–Meier method and then compared using the log-rank test. RESULTS: Patients with elevated pre-treatment alkaline phosphatase (>110 IU/L) had significantly worse progression-free survival (P<0.001) and overall survival (P<0.001) than those with a normal level of this marker (≤110 IU/L). Patients with elevated post-treatment alkaline phosphatase had worse progression-free survival (P<0.001) and overall survival (P<0.001) compared with those with a normal level. Patients with normal pre-treatment and post-treatment alkaline phosphatase showed the most favorable prognosis. The Cox multivariate analysis revealed that only the pre-treatment and post-treatment alkaline phosphatase levels were independent prognostic factors for progression-free survival (HR ϝ 1.656, P<0.001; HR ϝ 2.226, P<0.001) and for overall survival (HR ϝ 1.794, P<0.001; HR ϝ 2.657, P<0.001). CONCLUSIONS: Serum alkaline phosphatase appears to be a significant independent prognostic index in patients with skeletal metastatic nasopharyngeal carcinoma, which could reflect the short-term treatment response of palliative chemotherapy and the long-term survival outcomes.